CONCEPTUAL PRINCIPLES OF LAND RESOURCE MANAGEMENT IN THE AGRARIAN SECTOR OF THE ECONOMY OF UKRAINE - POLTAVETS, ANATOLII (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article substantiates the conceptual principles of land resource management in the agrarian sector of the Ukrainian economy. Modern conditions require the development of new conceptual approaches to the implementation of land resource management processes on the basis of taking into account the conditions of transformation of land ownership relations, the requirements of ensuring sustainable development and modern trends of strengthening the role of management bodies. It has been established that the management of land resources at the regional and national levels, in general, can be defined as the development and approval by state authorities and local self-government of a system of benefits and restrictions in land use for subjects of land relations, as well as control over compliance with regulatory prescriptions. The state land cadastre is the basis of the organization of management of the use of land resources. The knowledge of the application of the state land cadastre as the main tool for organizing the management of the use of land resources at the state level is substantiated. The essence and interrelationship of the economic and ecological component of the land resources management mechanism in the management system of agrarian enterprises is revealed. Contradictions in the characteristics of the management of the use of land resources as a system are outlined. It is proven that the management system of agricultural enterprises should combine the functions of cost monitoring of the land market, analysis of the efficiency of land use, and a set of measures for the rehabilitation of existing land resources as elements of the mechanism of sustainable land use. The criteria for the economic substantiation of measures within the framework of the land resource management mechanism in the management system of agrarian enterprises are outlined.
Keywords: land resources; management; state regulation; land cadastre; management mechanisms